#### Answer

The sweater cost 14 dollars, the blouse cost 10 dollars, and the skirt cost 48 dollars.

#### Work Step by Step

We call w the cost of a sweater, b the cost of a blouse, and k the cost of a skirt. Thus, we know:
$ k + w = 6b + 2 \\ k = 2(b + w) \\ k + b + w = 72$
First, using equations two and three, we substitute k/2 for b+w:
$ k + k/2 = 72 \\ k = 48$
This means:
$ 24 = b+ w \\ w = 24 -b$
We plug this into equation one to find:
$ 48 + 24 - b = 6b +2 \\ 7b = 70 \\ b = 10$
Thus:
$w = 24 - b = 24 - 10 = 14$